Ekspresi puitik sakral pada bentuk arsitektur Gereja Protestan di Indonesia bagian Barat (GPIB) Paulus di Jakarta - Tine Abrianti; Purnama Salura (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2019)
Sacred poetic expression on the architectural form of Gereja Protestan di Indonesia bagian Barat (GPIB) Paulus in Jakarta Church architecture shows the expression of its functions in layers. The first layer can be captured in a perception through its expression indicating sacred functions. The next layer was captured associatively on its influenced expression of church tradition and ideology. In the highest layer the sacred expression is displayed poetically. The poetic expression appearing in church architecture strongly supports its sacred functions. The nature of poetic that evokes the feeling and evoked imagination fits perfectly with the sacred functions of the Church as a threshold that marks the differences of the profane and sacred worlds, to deliver the congregation to God that is worshipped. The study aims to trace the entire relationship between the architectural form and space of the GPIB Paulus church with the sacred poetic expression shown. The results of the study are expected to add to the concept of church architecture as well as for related research. The method used in this study was first, redrawing the building of GPIB Paulus Church, to gain an understanding of the right architectural form. Second, analyze the appearance of church architecture shapes. The analysis based on the reference to read the sacred poetic expression, which is formulated through the elaboration of the concept of layers of sacred poetic in the architectural properties and compositions in each scope of architecture, covering the scope of environment, scope of site, scope of building, and scope of shape. Based on analysis results can be traced the concept of sacred poetic meanings to the architecture of Paul’s Church. The results concluded that the architecture of Paul's Church within the scope of site, building and shape featured a sacred expression at the level of perception and associative. In the scope of environment, the Church of Paul displays sacred expressions at the level of the poetic, expressed from the shape of the building. The proportion of the cross-shaped roof with the tower contrasts in a landscape setting in front of it, awakening the imagination of the dwelling of God in the highest places. © 2019 Tine Abrianti, Purnama Salura